ANALISIS PENGARUH CURRENT RATIO, RETURN ON ASSETS, DEBT TO EQUITY RATIO, DAN TOTAL ASSETS TURN OVER TERHADAP PERTUMBUHAN LABA PERUSAHAAN PERTAMBANGAN BATU BARA TAHUN 2017-2022 DENGAN COMPANY SIZE SEBAGAI VARIABEL MODERASI - Wiguna, Nanda Shautiya; Hakim, Lukman (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to analyze the effect of current ratio, return on assets, debt to equity ratio, and total assets turn over on profit growth of coal mining companies in 2017-2022 with company size as a moderating variable.  This research method is quantitative. This research data is secondary data. The secondary data used in this study consists of published financial reports of mining companies.  In addition, the official website of the Indonesia Stock Exchange (IDX). The population in this study were coal sector mining companies in the 2017-2020 period, totaling 5 of the 19 coal sector companies on the Indonesia Stock Exchange (IDX).  In this study, the sampling used was purposive sampling technique.  .  This research data analysis technique with the help of SPSS software.  The results of this study are that the Current ratio has a significant impact and has a negative effect on the profit growth of coal companies. Return on assets has a negative and significant effect on the profit growth of coal companies. Debt to equity ratio has a positive and significant impact on profit growth. Total assets turnover has a positive but insignificant impact on earnings growth. Company size cannot moderate the current ratio on the profit growth of coal companies. Company size is able to moderate the impact of return on assets on the profit growth of coal companies. Company size is able to moderate the debt to equity ratio on the profit growth of coal companies. Company size is unable to moderate total assets turnover on the profit growth of coal companies